Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1159/000368982
|View full text |Cite
|
Sign up to set email alerts
|

Low Plasma ApoE Levels Are Associated with Smaller Hippocampal Size in the Alzheimer's Disease Neuroimaging Initiative Cohort

Abstract: Apolipoprotein E (APOE) genotype is the strongest known genetic risk factor for sporadic Alzheimer's disease (AD), but the utility of plasma ApoE levels for assessing the severity of underlying neurodegenerative changes remains uncertain. Here, we examined cross-sectional associations between plasma ApoE levels and volumetric magnetic resonance imaging indices of the hippocampus from 541 participants [57 with normal cognition (NC), 375 with mild cognitive impairment (MCI), and 109 with mild AD] who were enroll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 54 publications
(73 reference statements)
1
21
0
Order By: Relevance
“…Low plasma apoE is associated with a decrease in hippocampal volume, and shows less of a sex difference in concentration levels in ɛ4 individuals than between the other genotypes (179). However, normal ɛ4 men show greater AD-pathology and worse memory performance than normal ɛ4 women, pointing to an earlier incidence of vulnerability (127).…”
Section: Sex Differences In Apoe Genotype and Risk Of Alzheimer’smentioning
confidence: 99%
“…Low plasma apoE is associated with a decrease in hippocampal volume, and shows less of a sex difference in concentration levels in ɛ4 individuals than between the other genotypes (179). However, normal ɛ4 men show greater AD-pathology and worse memory performance than normal ɛ4 women, pointing to an earlier incidence of vulnerability (127).…”
Section: Sex Differences In Apoe Genotype and Risk Of Alzheimer’smentioning
confidence: 99%
“…In human brains, APOE is normally synthesized and secreted by astrocytes and microglia and binds to high-density lipoproteins to facilitate cholesterol and phospholipid transport to LDL receptors. Low plasma APOE and APOE4 genotype are associated with morphological changes to the hippocampus, specifically reductions in size [16, 17]. Mouse models for studying both Apoe function and the human APOE variants have been created and have highlighted a complex role for APOE in the aging and diseased brain.…”
Section: Creating Animal Models For Late-onset Alzheimer’s Diseasementioning
confidence: 99%
“…Comparing to ApoE ε3, the ApoE ε4 isoform is more susceptible to proteolysis, leading to the accumulation of reactive fragments of ApoE ε4 in the cytosol, which results in cytoskeleton damage and neurodegeneration [8,9]. Teng et al [10] demonstrated that low plasma ApoE levels are significantly correlated with a smaller hippocampal size in patients with normal recognition or cognitive impairment. The authors claim that the plasma ApoE level may represent a peripheral marker of underlying AD in nondemented elderly individuals [10].…”
Section: Introductionmentioning
confidence: 99%
“…Teng et al [10] demonstrated that low plasma ApoE levels are significantly correlated with a smaller hippocampal size in patients with normal recognition or cognitive impairment. The authors claim that the plasma ApoE level may represent a peripheral marker of underlying AD in nondemented elderly individuals [10]. Many studies proved a contribution of APOE ε4 in the extracellular deposition of β-amyloid (Aβ), being a hallmark of AD.…”
Section: Introductionmentioning
confidence: 99%